Survey of prothioconazole sensitivity in Fusarium pseudograminearum isolates from Henan Province, China, and characterization of resistant laboratory mutants - Feng Zhou; Yan Jiao; Aohui Han; Xiaoli Zhou; Jiamei Kong; Haiyan Hu; Runqiang Liu; Chengwei Li (BMC Plant Biology, 2024)
Abstract Background Fusarium crown rot (FCR) is one of the most significant diseases limiting crop production in the Huanghuai wheat-growing region of China. Prothioconazole, a triazole sterol 14α-demethylation inhibitor (DMI) fungicide developed by the Bayer Crop Protection Company, is mainly registered for the prevention and control of wheat powdery mildew and stripe rust (China Pesticide Information Network). It is known to exhibit high activity against F. pseudograminearum, but further research, particularly regarding the potential for fungicide resistance, is required before it can be registered for the control of FCR in China. Results The current study found that the baseline sensitivity of 67 field isolates of F. pseudograminearum collected between 2019 and 2021 ranged between 0.016–2.974 μg/mL, with an average EC50 value of 1.191 ± 0.720 μg/mL (mean ± SD). Although none of the field isolates exhibited signs of resistance, three highly resistant mutants were produced by repeated exposure to prothioconazole under laboratory conditions. All of the mutants were found to exhibit significantly reduced growth rates on potato dextrose agar (PDA), as well as reduced levels of sporulation, which indicated that there was a fitness cost associated with the resistance. However, inoculation of wounded wheat coleoptiles revealed that the pathogenicity of the resistant mutants was little affected or actually increased. Molecular analysis of the genes corresponding to the prothioconazole target protein, FpCYP51 (FpCYP51A, FpCYP51B, and FpCYP51C), indicated that the resistant mutants contained three conserved substitutions (M63I, A205S, and I246V) that were present in the FpCYP51C sequence of all three mutants, as well as several non-conserved substations in their FpCYP51A and FpCYP51B sequences. Expression analysis revealed that the presence of prothioconazole (0.1 μg/mL) generally resulted in reduced expression of the three FpCYP51 genes, but that the three mutants exhibited more complex patterns of expression that differed in comparison to their parental isolates. The study found no evidence of cross-resistance between prothioconazole and any of the fungicides tested including three DMI fungicides tebuconazole, prochloraz, and flutriafol. Conclusions Taken together these results not only provide new insight into the resistant mechanism and biological characteristics associated with prothioconazole resistance in F. pseudograminearum, but also strong evidence that prothioconazole could provide effective and sustained control of FCR, especially when applied in combination with other fungicides.